Sarcopenia and its associated factors in Iranian older individuals: Results of SARIR study. (September 2016) - Hashemi, Rezvan; Shafiee, Gita; Motlagh, Ahmadreza Dorosty; Pasalar, Parvin; Esmailzadeh, Ahmad; Siassi, Fereydoun; Larijani, Bagher; Heshmat, Ramin
Highlights: Lower body weight, BMI, WC, and skeletal muscle index at any three stages of sarcopenia. Significant lower grip strength and gait speed among severe sarcopenic group. Higher prevalence of sarcopenia among the oldest group (above 75 years old). Abstract: Background: Sarcopenia, an age- related loss of muscle mass, is a significant associating factor for functional impairment among older adults. The aim of this study was to investigate the prevalence of and associated factors for sarcopenia and severe sarcopenia among older adults in Iran. Methods: A total of 300 individuals aged over 55 years were randomly selected from the 6th district of Tehran, Iran, in 2011. Sarcopenia was defined according to the European Working Group on Sarcopenia in Older People (EWGSOP) algorithm. The skeletal muscle mass was assessed using DXA. Muscle strength and muscle performance were assessed according to hand grip strength and 4-m usual walking gait speed test. A logistic regression analysis was performed. Results: The prevalence values of presarcopenia, sarcopenia, and severe sarcopenia were 52.7%, 20.7%, and 6%, in men and 25.3%, 15.3%, and 5.3% in women, respectively. The prevalence of sarcopenia was higher in men older than 75 years than women in the same age range (36.7% versus 20%, respectively). Using multiple logistic regression models, age, sex, smoking, and body mass index (BMI) were independently associated with different stages of sarcopenia. Conclusions: The prevalence of sarcopenia is high in Iranian older adults. The older age, male sex, smoking and lower BMI were independently associated with presarcopenia, sarcopenia and severe sarcopenia.